2020
DOI: 10.3390/ijms21239173
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-Dependent Regulation of TRPs Expression in Trigeminal Ganglion Neurons Attenuates Orofacial Neuropathic Pain following Infraorbital Nerve Injury in Rats

Abstract: We evaluated the mechanisms underlying the oxytocin (OXT)-induced analgesic effect on orofacial neuropathic pain following infraorbital nerve injury (IONI). IONI was established through tight ligation of one-third of the infraorbital nerve thickness. Subsequently, the head withdrawal threshold for mechanical stimulation (MHWT) of the whisker pad skin was measured using a von Frey filament. Trigeminal ganglion (TG) neurons innervating the whisker pad skin were identified using a retrograde labeling technique. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Due to the obstruction of epineurium and blood-nerve barrier, the concentration of drugs reaching the nerve injury is not high ( 16 ), such that nanopore-mediated degradable materials are attached to the optic nerve to increase the concentration of drugs and promote nerve recovery. NGF increases the activity of nerve growth factor in the injured nerve by acting on the high-affinity receptor tyrosine kinase and low-affinity receptor of effector cells regulates the microenvironment for the survival of neurons, protects the survival of neurons, and promotes myelin repair ( 17 , 18 ). Triamcinolone acetonide prevents adhesion and scar formation by reducing exudation and edema in the early stage of inflammation, inhibiting free radical damage, and reducing capillary permeability in the later stage of inflammation ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the obstruction of epineurium and blood-nerve barrier, the concentration of drugs reaching the nerve injury is not high ( 16 ), such that nanopore-mediated degradable materials are attached to the optic nerve to increase the concentration of drugs and promote nerve recovery. NGF increases the activity of nerve growth factor in the injured nerve by acting on the high-affinity receptor tyrosine kinase and low-affinity receptor of effector cells regulates the microenvironment for the survival of neurons, protects the survival of neurons, and promotes myelin repair ( 17 , 18 ). Triamcinolone acetonide prevents adhesion and scar formation by reducing exudation and edema in the early stage of inflammation, inhibiting free radical damage, and reducing capillary permeability in the later stage of inflammation ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…injection of medetomidine (0.15 mg/kg; Zenoaq), midazolam (2.0 mg/kg; Sandoz), and butorphanol (2.5 mg/kg; Meiji Seika Pharma). IONI was performed in compliance with previous studies (Ando et al, 2020). Briefly, the left buccal mucosa was intraorally incised by a scalpel along the alveolar ridge about 10‐mm.…”
Section: Methodsmentioning
confidence: 99%
“…This pain occasionally spreads to the intact orofacial area beyond the area innervated by the injured trigeminal nerve afferents, and relieving the orofacial pain symptoms can be challenging for clinicians (Renton et al, 2012). Recently, a rodent model that develops orofacial neuropathic pain due to infraorbital nerve injury (IONI) has been established to identify effective treatments for orofacial pain (Ando et al, 2020; Shinoda et al, 2007). Studies using the IONI model elucidate the pathogenic mechanism of orofacial neuropathic pain, but the detailed mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that OXT could interact with V1A-R, which is upregulated following nerve injury and with certain K + channels, which are also functionally changed after nerve injury to exert its analgesic effects. Results from yet another study suggested that OXT application to the nerve-injured site attenuated ION injury-induced mechanical hypersensitivity by inhibition of the TRPV1 and TRPV4 expression in neurons innervating the whisker pad skin [ 137 ]. Finally, it has been shown that administration of oxytocin into rats’ TG-activated oxytocin receptors, attenuated orofacial ectopic pain and inhibited the upregulation of OXTR, calcitonin gene-related peptide (CGRP), IL-1B and TNFa in the TG as well as at the spinal trigeminal nucleus caudalis (SpVc) of rats exposed to inferior alveolar nerve transection [ 138 ].…”
Section: Peripheral Events In the Pathophysiology Of Ptnpmentioning
confidence: 99%